The Influence of Board Size, Institutional Ownership, and Firm Size on Merger and Acquisition Performance (An Empirical Study of Companies Listed on The Indonesia Stock Exchange in 2019–2023) - Ni Made Dyana Amritaloka; Ni Ketut Rasmini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Data from the Business Competition Supervisory Commission (KPPU) indicate that the impact of COVID-19 in 2020, 2021, and peaking in 2022 led to a significant increase in merger and acquisition (M&A) activities. This trend suggests that M&A actions have become an essential strategy for sustaining and enhancing business performance. However, not all M&A activities result in success, making it crucial to understand the factors influencing their outcomes. This study aims to examine and provide empirical evidence on the effect of board size, institutional ownership, and firm size on merger and acquisition performance. Agency theory and signaling theory are employed as the theoretical frameworks to explain the relationships between the independent and dependent variables. The population of this study consists of publicly listed companies that conducted mergers and acquisitions between 2019 and 2023. The sampling technique used was purposive sampling, resulting in a total of 150 samples. Data were collected through non-participant observation, and the data analysis technique applied was multiple linear regression. The results show that institutional ownership has a positive effect on merger and acquisition performance. In contrast, board size and firm size do not significantly influence M&A performance. These findings indicate that monitoring by institutional shareholders can enhance the effectiveness of strategic decision-making, while a larger organizational structure and firm size do not necessarily support post-merger integration success.